CURRENT PROBLEMS OF THE DEVELOPMENT OF PHYSICAL CULTURE AND SPORTS IN CRISIS CONDITIONS: A REVIEW AND ANALYTICAL STUDY (Physical Culture and Sport: Scientific Perspective, 2025)
The COVID-19 pandemic and the full-scale war in Ukraine have created overlapping crises that significantly affect public health, physical activity patterns, sport systems and the education sector. Purpose: This narrative review-analytical paper synthesizes empirical studies, systematic reviews and official reports to examine how pandemic-related restrictions and wartime conditions have changed population physical activity, the state of physical culture, and elite sport in Ukraine, and to propose policy and practice pathways for recovery and resilience. Methods: A structured literature search was performed in PubMed, Scopus, Web of Science, Google Scholar and Ukrainian repositories, supplemented by UN, UNESCO and national government documents; the selection and reporting followed PRISMA principles. Results: Evidence indicates a substantial decline in overall physical activity and increases in sedentary behaviour during pandemic lockdowns, with consequent deterioration in health-related fitness among children, adolescents, and university students. The subsequent war amplified vulnerabilities: damage to sports infrastructure, displacement of youth and athletes, loss of coaching and medical personnel, disruptions to training/competition cycles and elevated mental health burden. These combined shocks threaten both mass physical activity levels and the preparation pipeline for elite performance. Conclusions: Recovery requires integrated measures – immediate restoration of accessible facilities, targeted programs for youth physical activity (including digital/hybrid solutions), psychological support for affected populations, targeted assistance for elite athletes (training abroad, scholarships) and alignment of national PE and sport policies with WHO physical activity guidelines. Long-term resilience depends on intersectoral coordination, sustainable financing and evidence-based monitoring of population activity and fitness. Recovery requires multi-stakeholder coordination, evidence-based policy and investment in resilient, inclusive PA and sport systems.
Keywords: crisis situations; physical activity; physical culture; sports; schoolchildren; student youth; athletes